Letter from Max Bredig to Georg Bredig, June 12, 1936 - Bredig, Max Albert (1936)
This letter, the majority of which is illegible, was written by Max Bredig (1902-1977) to his father Georg Bredig (1868-1944).
Keywords: Bredig, Max Albert, 1902-1977; Bredig, Georg, 1868-1944